Mixed Methods in Early Childhood Special Education Research: Purposes, Challenges, and Guidance. (March 2020) - Corr, Catherine; Snodgrass, Melinda R.; Greene, Jennifer C.; Meadan, Hedda; Santos, Rosa Milagros
Mixed methods approaches to research are gaining popularity in the social sciences. Although these approaches may be unfamiliar to many in our field, they can uniquely contribute to and enhance early childhood special education (ECSE) research. The purpose of this article is to orient ECSE researchers to the field of mixed methods social inquiry. We offer two examples of mixed methods. We define mixed methods and how mental models and paradigms influence these efforts, including a discussion of the distinctive purposes for applying mixed methods. Finally, we identify challenges to determining rigor and quality of mixed methods research and offer preliminary guidance to mitigate these challenges. Throughout, we encourage integrating rigorous mixed methods into ECSE scholarship.